Grammatical Problems In The Student's Writing At The Second Year Of SMA 1 Brebes - Pratiwi, Atina Tati (2008)
This research aims at describing grammatical problems focused on the types of errors and sources of errors in the student's writing at the second year of SMA 1 Brebes in 2007/2008 academic year. This research is a descriptive qualitative study in which the data are the result of writing test. The techniques of collecting data are test of writing for students and the document. The technique for analyzing data are classifying the data, describing the type of error based on surface strategy taxonomy (omission, addition, misformation, and misordering) which include grammatical rules, categorizing the error based on it's error category in the form of table and calculating the amount of each category in order to find out the dominant type of error, and finding out the frequency of errors based on the table. The study shows the types o errors are: a). omission (40 errors or 45,45 %) b). addition (15 errors or 17,08 %), c). misformation (26 errors or 29,54 %), d). misordering (7 errors or 7,95 %). The result of the research shows that the dominant errors in the case of grammatical rule is the omission of simple present tense indicator that contains 18 errors or 20,39 %. The highest frequency of errors cased on the surface strategy taxonomy is omission errors with the total number of errors 40 or 45,45 %. The sources of errors are: a). interlingual language (50 errors or 56,81 %) b). intralingual language (38 errors or 43,22 %). The interlingual transfer is the error caused by mother tongue influence. Meanwhile, The intralingual transfer is the error caused by the target language influences. The dominant source of error is caused by interlingual transfer in omission of -s/-es in simple present tense (12 error or 13,6 %).